(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In 135 students permanently residing in low and high mountains, the physiological status of the immune system was studied depending on the area of residence before moving due to study, and at the end of the first year of study. The content of leukocytes, lymphocytes with CD4+, CD3+, CD56+, CD16+, CD19+ receptors in the peripheral blood was determined on a Beckman Coulter flow cytometer (USA), and the leukogram (leukocyte formula) was examined.It was shown that in students of both groups the content of leukocytes and lymphocytes in the peripheral blood is within the reference values, but in the representatives of the highlands it is at the upper limit of the physiological norm, and among the lowlanders it is at the lower limit.At the same time, there is a deficiency in the content of T- and B-lymphocytes in those living in low mountains, and in representatives of high mountains there are changes in the population of ECs and helpers, which are compensated by the end of the first year of study. In the leukocyte formula, 18% of the Highlanders have a slight monocytosis, and 25% of the Lowlanders have eosinophilia, which is minimized by the end of the first course. According to the changes in indicators, it can be stated that deviations from the generally accepted limits of fluctuations in immunological parameters affect the effectiveness of students’ immune protection, and living in high mountains from the moment of birth contributes to the formation of a higher level of immune health.